A New European Bauhaus for a Culture of Transversality and Sustainability - María Jesús Rosado-García (MDPI AG, 2021)
This article provides a critical study of a New European Bauhaus initiative in the context of transversality, relational nature and sustainability of construction, architecture and civil engineering. Social and environmental factors in this ecosystem of innovation are highlighted, as well as the perspectives of actors within it. The relationships between art, technology and science of historical Bauhaus are assessed. The investigation of transversality was carried out using a visual tool developed by the authors, CATI, considering sustainability as the backbone. The New European Bauhaus is a pool of innovation that is supported by governments, academia, industry, society and the (natural) environment. It aims at social, environmental and cultural sustainability and includes ideas of social transformation. It is necessary to absorb the impact and overwhelming cultural consequences of previous and current Industrial Revolutions, principally relying on cyber–physical systems to generate spaces and collective intelligence. The climate crisis and the COVID-19 pandemic have increased the need for new approaches, expanding the concept of smart cities to smart territories, taking into account participation in society and general inclusivity.